THE EFFECT OF UTILIZING THE COLLECTION OF ECONOMIC LITERATURE, READING INTEREST AND LEARNING DISCIPLINE ON LEARNING ACHIEVEMENT - Pratiwi, Novika Sri (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to analyze the effect of using a collection of economic literature, reading interest and learning discipline on learning achievement. The method used in this study is a quantitative method. The sample was 179 students of the Faculty of Economics, State University of Jakarta. The sampling technique is proportional random sampling. The data analysis technique used is path analysis. The results of this study are: 1) Utilization of a collection of economic literature has a positive and significant effect of 15.6% on learning achievement, 2) reading interest has a positive and significant effect of 61.2% on learning achievement, 3) learning discipline has a positive and significant effect. by 14.6% on learning achievement, 4) Utilization of economic literature collections, reading interest and learning discipline together have a positive and significant effect of 64.5% and the rest are influenced by other factors.